Encaixe narrativo e processos ideológicos na obra de Eliane Potiguara - Lima, Danielle dos Santos Pereira (2018)
In this dissertation we have as object of study the work of Eliane Potiguara, constituted by a novel book and three short stories, which are produced in the interstices of western and indigenous literature. The work addresses the testimony of indigenous peoples of different ethnicities and highlights the figure of the indigenous grandmother as a "guardian" of collective memory. The old woman plays the social and cultural role of renifying the ancestral past from storytelling. The presence of the grandmother in the writing of Eliane Potiguara is striking and founds the autobiographical pact of the work. In addition, this figure is responsible for performing the role of man-narrative in the stories, recalling stories of oral literature, which are inserted into the main plot, forming narrative fittings. In this sense, in chapter 1: we highlight the theoretical-critical approach to the concept of fitting and the presence of this phenomenon in the tale The Coconut that kept the night (2012). In chapter 2: we discuss the construction of the autobiographical pact and the meta-chronic character of the short stories The Enchanted Bird (2014) and The Cure of the Earth (2015). In chapter 3: we reflect on the binarism of revide in Half Face, Half Mask (2004) and we seek to deconstruct the myth of the native protector from a comparative study between the characters Cunhataí and Nará-Sué Uarená, by Nenê Macaggi (2012). In short, based on a perspective based on theories of memory, literature and culture, we infer that the work of Eliane Potiguara refers to social memory as an instrument of retaliation and indigenous identity affirmation.